Radiation Belt Daily Average Electron Flux Model (RB‐Daily‐E) From the Seven‐Year Van Allen Probes Mission and Its Application to Interpret GPS On‐Orbit Solar Array Degradation. Issue 11 (8th November 2022) - Gabrielse, Christine; Lee, Justin H.; Claudepierre, Seth; Walker, Don; O'Brien, Paul; Roeder, James; Lao, Yao; Grovogui, Jann; Turner, Drew L.; Runov, Andrei; Boyd, Alexander; Fennell, Joseph; et al.
Abstract: We use NASA's Van Allen Probes data to build a 3‐dimensional Radiation Belt Daily Average Electron flux model (RB‐Daily‐E) covering 25 differential energies (33–7, 700 keV), 17 pitch angles, and a variable number of L shells from 2 to 7. RB‐Daily‐E can be used to deduce the fluences observed by any satellite that flew within Van Allen Probes' 7‐year mission lifetime. We supplement Van Allen Probes fluxes with THEMIS average fluxes to cover higher L shells when applying the model to a secondary satellite. RB‐Daily‐E agrees with both the Arase high‐energy electron experiment (XEP) flux data and the GPS Combined X‐ray Dosimeter (CXD) electron flux approximately within a factor of two or better, and comparisons with AE9 are as expected. The RB‐Daily‐E Model has applications for when actual fluxes on day‐timescales are required for post‐anomaly investigations, including long‐term radiation environment effects such as solar cell and solar array degradation. We therefore applied the model to two GPS satellites to determine electron fluence inputs to the Equivalent Flux (EQFLUX) solar cell degradation model. The modeled voltage degradation well‐matched the voltage degradation trends identified in the GPS telemetry data, suggesting that the radiation environment is the primary cause of the voltage degradation. The current degradation was largely underestimated, suggesting that current degradation is influenced by other sources. Plain Language Summary: Most industry‐standard data‐informed radiation environment models rely on statistics, which may not accurately describe the environment on a specific day. These models are used to characterize the radiation environment to determine expected degradation rates of solar array voltages and currents in space, which is important for satellite power and lifetime. A well‐known conundrum is that the expected degradation underestimates the actual degradation, raising questions about whether the radiation environment is correctly modeled or if there are other contributing factors not correctly included in degradation predictions. This paper describes a new model that estimates the electron radiation for a given day in any given orbit using data from NASA's Van Allen Probes and THEMIS missions. Comparisons to spacecraft data demonstrate the model's robustness. The new model and standard radiation models were both applied to estimate the solar array voltage and current degradation on multiple GPS satellites and compared to actual degradation. The results of the 3‐way comparison showed that the new model produces superior solar array voltage degradation estimates, demonstrating that radiation is practically the sole source of voltage degradation, and provides conclusive evidence that factors in addition to radiation need to be accounted for when estimating the solar array current. Key Points: The Radiation Belt Daily Average Electron flux model (RB‐Daily‐E) built on Van Allen Probes and THEMIS data is consistent with GPS CXD and Arase data RB‐Daily‐E applied to GPS orbit determined that the radiation environment is the prime contributor to GPS solar array voltage degradation RB‐Daily‐E applied to GPS orbit determined that the radiation environment is a minor contributor to GPS solar array current degradation